Pelayanan PT. PLN (PERSERO) Unit Layanan Pelanggan (ULP) Panam Dalam Menanggapi Keluhan Pelanggan - Chesa Clara Chameria; Abdul Sadad (Pusat Riset dan Inovasi Nasional, 2024)
Indonesia is one of the developing countries, to carry out fair and equitable development throughout Indonesia, there is a need for sufficient energy as a driving motor for development itself. Electricity distribution in Pekanbaru, as in other regions of Indonesia, is handled by the State Electricity Company (PLN) as the largest electricity supply company in Indonesia. PT. PLN (Persero) Pekanbaru ULP Panam branch as one of SOEs that aims to provide services in the field of electricity to the community (Public Utility). Organizational structure that is a primary and absolute requirement for increasing employment, responsibility and achievement of established goals. The purpose of this study is to describe and analyze PT.PLN services in handling customer complaints and identify and analyze the inhibitory factors of PT.PLN services in handling customer complaints. This study used Zeithaml's theory of five indicators: Tangible, Reliability, Responsiveness, Assurance, Emphathy. The methods used in this study are qualitative research methods that are descriptive. With data collection techniques, observation interviews and documentation. The service provided by PLN ULP Panam is still insufficient because of the many customer complaints that resulted in the service process being hampered. The service provided by the officers is not sufficient in responding to customer complaints and the SOP or Service Standards for officers in handling customer complaints do not exist. PLN ULP Panam must take this problem seriously because if there is no SOP or Service Standard, it is detrimental to the service process provided to customers.